Exploring Design Guidelines of Tangible Interaction in Learning for Children with Dyslexia - Nurliana Jamali, Siti; Admodisastro, Novia; Azim Abd Ghani, Abdul; Hassan, Sa’adah; Kamaruddin, Azrina; Suhaila Abdul Hamid, Siti (International Journal of Engineering and Technology, 2018)
Tangible Interaction (TI) has shown many benefits in various situations for it provides more direct manipulations and haptic feedback. In addition, TI also provide a more enjoyable learning environment.Â Despite active research in TI, there is limited research on design learning, particularly associated with the TI for children with dyslexia. Current approaches are found to still depend on traditional multisensory teaching materials. However, some literatures argued that the use of traditional multisensory teaching materials used in the current teaching technique is less attractive, lack sense, offer no feedback such as sound and only rely heavily on the teacher. A preliminary study was conducted to understand better how TI works for children with dyslexia. The study is conducted by the research team using a semi-structured interview and observations with teachers who teach dyslexic children.Â In this paper, an investigation of the teaching materials and learning approaches used in the Dyslexia Association of Malaysia (DAM) learning centre to support children with dyslexia were studied and analysed. Finally, design guidelines are constructed and proposed based on the data obtained from the study conducted. The design guidelines will be adopted to develop a tangible interaction between the learning model and its prototype for children with dyslexia.Â